2010
DOI: 10.1152/ajpcell.00422.2009
|View full text |Cite
|
Sign up to set email alerts
|

Acetylsalicylic acid enhances purinergic receptor-mediated outward currents in rat megakaryocytes

Abstract: Young JP, Beckerman J, Vicini S, Myers A. Acetylsalicylic acid enhances purinergic receptor-mediated outward currents in rat megakaryocytes. Am J Physiol Cell Physiol 298: C602-C610, 2010. First published December 30, 2009 doi:10.1152/ajpcell.00422.2009.-Purinergic receptor activation increases cytosolic Ca 2ϩ concentration in a fluctuating fashion, triggering oscillatory outward Ca 2ϩ -activated K ϩ currents in rat megakaryocytes (MKs). Whole cell and nystatinperforated patch-clamp techniques were used to an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 54 publications
(82 reference statements)
1
2
0
Order By: Relevance
“…Therefore, we applied a higher concentration of aspirin than normally used for in vitro studies. 17,18 Similar to the effects of other NSAIDs on thymocytes, 12 aspirin suppressed the Kv1.3channel currents in the megakaryocytes (Figure 1Ba). Since it significantly lowered the peak (from 66.9 + 11.9 to 19.2 + 1.46 pA/pF, n ¼ 6, P < .05; Figure 2Bb) and the pulse-end currents (from 40.5 + 6.47 to 16.4 + 1.79 pA/ pF, n ¼ 6, P < .05; Figure 2Bc), the suppression pattern was similar to that of indomethacin, 12 showing a ''C-type inactivation'' pattern in the kinetic studies.…”
Section: Effects Of Aspirin On Kv13-channel Currents In Rat Megakarysupporting
confidence: 56%
“…Therefore, we applied a higher concentration of aspirin than normally used for in vitro studies. 17,18 Similar to the effects of other NSAIDs on thymocytes, 12 aspirin suppressed the Kv1.3channel currents in the megakaryocytes (Figure 1Ba). Since it significantly lowered the peak (from 66.9 + 11.9 to 19.2 + 1.46 pA/pF, n ¼ 6, P < .05; Figure 2Bb) and the pulse-end currents (from 40.5 + 6.47 to 16.4 + 1.79 pA/ pF, n ¼ 6, P < .05; Figure 2Bc), the suppression pattern was similar to that of indomethacin, 12 showing a ''C-type inactivation'' pattern in the kinetic studies.…”
Section: Effects Of Aspirin On Kv13-channel Currents In Rat Megakarysupporting
confidence: 56%
“…Limited data suggest that thrombin and ADP may enhance megakaryocyte maturation and platelet formation. Megakaryocytes express P2Y 12 , P2Y 1 , and P2X 1 receptors that can mediate responses to ADP [e.g., generation of Ca 21 currents and binding to fibrinogen (120,121)] implicated in megakaryocyte maturation and platelet formation (122). Thrombin may also induce megakaryocyte maturation, as suggested by changes in Ca 21 signaling, morphology, activation of pathways associated with platelet formation, secretion of a-granule proteins, and increase in VEGF secretion (123)(124)(125)(126).…”
Section: A Role For Megakaryocytes In Covid-19?mentioning
confidence: 99%
“…It was shown that Sp1/3 and NF-1 mediate transcription of the human P2X1 receptor gene in megakarioblastic Meg-01 cells [394]. Acetylsalicylic acid, a cyclooxygenase-1 inhibitor and antithrombotic agent, enhanced P2Y receptor-mediated outward current in rat megakaryocytes [395]. ADP released by megakaryocytes regulates pro-platelet formation by human megakaryocytes via P2Y 13 receptors [396,397].…”
Section: Megakaryocytesmentioning
confidence: 99%